Indexes to Debates of the National Assembly (Hansard) - South Africa Parliament, House of Assembly (Cape Town Government Printers, 1995)
South Africa Parliament Debates of the National Assembly (Hansard).
South Africa Politics and government. Debates of the National Assembly. Continued in part by: Interpellations, questions and replies of the National Assembly. 21 cm
Keywords: Indexes to Debates; National Assembly; Hansard; Second Session - Firsts Parliament; 23 January; 11 October; 1995; Vol. 8; ISBN 0621169927; ISBN 0621169994; JC259032; Index to Speeches